Metabolites from the Marine-derived Fungi Pseudopestalotiopsis sp. PSU-AMF45 and Trichoderma Iongibrachiatum PSU-AMF274 - Haryadi Nugraha Putra (Prince of Songkla University, 2024)
Master of Science (Chemistry (International Program)), 2019